PERKEMBANGAN MOTORIK KASAR ANAK MELALUI KEGIATAN BERMAIN LEMPAR TANGKAP BOLA DI RA ASSYIFA - Mariani Harahap (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2020)
This study aims to determine the gross motor development of children through playing ball throwing activities in RA Assyifa. This study was conducted in RA Assyifa with 15 (fifteen) students, consisting of seven (7) girls and eight (8) children man. The benefit of this research is to develop aspects of gross motor development in early childhood. The technique or research method used is classroom action research. The results of this study are through the activity of throwing a ball catch this turns out to be able to improve gross motor skills by providing motivation to children and also giving opportunities to children to be able to do activities one by one in group B in RA Assyifa medan.